EXERCISE FOR DEPRESSION: A FEASIBILITY TRIAL EXPLORING NEURAL MECHANISMS - Gujral, Swathi (Am J Geriatr Psychiatry, 2019)
OBJECTIVE: To test the feasibility of an exercise augmentation to pharmacotherapy in depressed younger and older adults while exploring neural mechanisms. METHODS: A randomized, double-blind, controlled clinical trial was conducted in fifteen inactive younger (20–39 years) and older (60–79 years) adults meeting DSM-5 criteria for a major depressive episode (https://clinicaltrials.gov/ct2/show/NCT02407704). Participants were randomized to receive a 12-week regimen of venlafaxine XR or venlafaxine XR plus supervised exercise. Cardiorespiratory fitness was assessed using a submaximal VO(2) test and neuroimaging assessments were conducted using a 7-Tesla MR scanner. RESULTS: Attrition was 38% and 14% for the medication and exercise groups, respectively. Attendance was 91% for the exercise intervention. Exploratory analyses revealed an association between improvement in fitness and increased cortical thickness in the anterior cingulate cortex. CONCLUSION: Exercise augmentation to pharmacotherapy is feasible for depressed younger and older adults and may have neural benefits in a core brain region implicated in depression.